2017
DOI: 10.1002/adfm.201605593
|View full text |Cite
|
Sign up to set email alerts
|

Textile Resistance Switching Memory for Fabric Electronics

Abstract: A new type of wearable electronic device, called a textile memory, is reported. This is created by combining the unique properties of Al‐coated threads with a native layer of Al2O3 as a resistance switching layer, and carbon fiber as the counter‐electrode, which induces a fluent redox reaction at the interface under a small electrical bias (typically 2–3 V). These two materials can be embroidered into an existing cloth or woven into a novel cloth. The electrical resistance of the contacts is repeatedly switche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
54
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 43 publications
0
54
0
1
Order By: Relevance
“…The textile RRAM devices operated at voltages between −4 and +4 V with average on/off ratio of ≈10 2 . Furthermore, the textile RRAM devices were stably operated at room temperature up to 10 000 s. It was also demonstrated that the textile RRAM devices were reliable even after soaking in water with detergent for 10 min . In terms of mechanical stability, the textile RRAM devices showed stable operation in bent and twisted conditions (Figure e,f).…”
Section: Textile‐based Electronic Devices and Systemsmentioning
confidence: 79%
See 2 more Smart Citations
“…The textile RRAM devices operated at voltages between −4 and +4 V with average on/off ratio of ≈10 2 . Furthermore, the textile RRAM devices were stably operated at room temperature up to 10 000 s. It was also demonstrated that the textile RRAM devices were reliable even after soaking in water with detergent for 10 min . In terms of mechanical stability, the textile RRAM devices showed stable operation in bent and twisted conditions (Figure e,f).…”
Section: Textile‐based Electronic Devices and Systemsmentioning
confidence: 79%
“…f) Current–voltage characteristics of the linked 10 × 10 array with various deformations. c–f) Reproduced with permission . Copyright 2017, Wiley‐VCH.…”
Section: Textile‐based Electronic Devices and Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among emerging nonvolatile memory devices, resistive random access memory (RRAM) has attracted significant amounts of attention because it provides a variety of advantages, including flexibility, cost‐efficiency, and simple integration with high packing density levels . In this regard, various types of RRAM, based on organic/inorganic materials, have been reported for flexible memory in the form of copper wire network‐based memory, flexible memory arrays on plastic substrates, logic‐in‐memory on fabric substrates, memory on fabric with native aluminum oxide (Al 2 O 3 ), and graphene‐oxide‐based woven memory . However, a few certain limitations, such as complicated processes, the requirement of bulky equipment to provide the necessary high temperatures and vacuum condition, and poor reliability, continue to hinder practical applications of fabric‐based electronics …”
mentioning
confidence: 99%
“…Accordingly, the constituents (e.g., fibers or yarns) of textile products have been directly fashioned into electrical devices by incorporating appropriate functional design and materials. These include “fiber”‐shaped photovoltaic devices, transistors, logic circuits, sensors, actuators, other electronic/optical devices in addition to “fabric”‐based devices . Modulation of resistance and/or capacitance have been the two most common strategies to sense various physical stimuli, such as applied forces and moisture .…”
mentioning
confidence: 99%